Note sul rapporto tra politica e strategia a partire da "Teoria del partigiano" di Carl Schmitt - Giroldo, Luigi (Philosophy Kitchen - Rivista di filosofia contemporanea, 2015)
This article analyzes the Theory of Partisan - a book written by Carl Schmitt – focusing especially on the relation between politics and strategy in the so-called “revolution war”. The focus is centered on the spatial implication of this theory that emerged through the analysis of the role of the war in the state political order. In the final, this article suggests a new way to comprehend the meaning of the nomos utilizing Deleuze-Guattari’s thinking.